'Connecting hearing to viewing and knowing to feeling': Sound as evocation in non-fiction film with particular reference to No Escape (Cox, 2009). Issue 1 (11th August 2011) - Cox, Geoffrey
This article investigates the early historical context of the relationship between sound and image in film, and how contemporary theorists have drawn on this to suggest new creative aesthetic modes. The practical realization of such suggestions will be illustrated primarily by an analysis of my own film No Escape (Cox, 2009), which explores the combination of live piano music, diegetic sound and image. It draws on my collaborative work as sound designer and composer with film-maker Keith Marley, whereby we have attempted to challenge the perceived relationship between sound and image in documentary film (e.g. Cider Makers, Keith Marley, 2007 and A Film About Nice, Keith Marley and Geoffrey Cox, 2010), a relationship seen as stratified or hierarchical in the sense that sound is often treated by film-makers as subordinate to image in a genre that is dominated by what Bill Nichols calls a 'discourse of sobriety'.